Person-Centred Care Including Deprescribing for Older People - Heather Smith; Karen Miller; Nina Barnett; Lelly Oboh; Emyr Jones; Carmel Darcy; Hilary McKee; Jayne Agnew; Paula Crawford (MDPI AG, 2019)
There is concern internationally that many older people are using an inappropriate number of medicines, and that complex combinations of medicines may cause more harm than good. This article discusses how person-centred medicines optimisation for older people can be conducted in clinical practice, including the process of deprescribing. The evidence supports that if clinicians actively include people in decision making, it leads to better outcomes. We share techniques, frameworks, and tools that can be used to deprescribe safely whilst placing the person’s views, values, and beliefs about their medicines at the heart of any deprescribing discussions. This includes the person-centred approach to deprescribing (seven steps), which incorporates the identification of the person’s priorities and the clinician’s priorities in relation to treatment with medication and promotes shared decision making, agreed goals, good communication, and follow up. The authors believe that delivering deprescribing consultations in this manner is effective, as the person is integral to the deprescribing decision-making process, and we illustrate how this approach can be applied in real-life case studies.